VEGETATIVE PROPAGATION OF THE APPLE ROOTSTOCK ‘MARUBAKAIDO’ IN THE SEMI-ARID REGION OF MINAS GERAIS (REMUNOM, 2026)
Apple seedling production in the semi-arid region is incipient, so production techniques must be adapted. The objective was to evaluate the development of seedlings of the "Marubakaido" rootstock, obtained from cuttings of different diameters with lesions at the base and subjected to naphthaleneacetic acid. The research was carried out in 2 different experiments. For experiment 1, the design was a randomized complete block design (RCBD), arranged in a 2x2x2 factorial (2 cutting diameters, 2 types of basal cut and 2 doses of 1-naphthaleneacetic acid (NAA)). For experiment 2, an RCBD was used following a 2x2x5 factorial scheme (2 cutting diameters, 2 types of basal cut and 5 evaluation times). Both experiments contained four blocks and four cuttings per block. In experiment 1, after 150 days, the number of shoots and leaves, shoot length and diameter, leaf length, diameter and diagonal, percentage of sprouted, rooted and live cuttings, fresh and dry mass of shoots and roots, and root length and volume were evaluated. In experiment 2, the number of leaves and shoots, shoot length and diameter were evaluated every two weeks. In experiment 1, there was no significant interaction between the tested factors, only an isolated effect for each factor. The variables leaf length and diagonal differed significantly in relation to the diameter of the cuttings used. The type of cut did not show a significant effect for all variables. Significance was obtained using NAA for root fresh mass. In experiment 2, a significant interaction was found between the type of cut and evaluation time for the number of shoots. Shoot length and diameter and number of leaves showed significance in relation to the evaluation time. The ‘Marubakaido’ variety shows good rooting and seedling development in Northern Minas Gerais.